Surface behavior, aggregation and phase separation of aqueous mixtures of dodecyl trimethylammonium bromide and sodium oligoarene sulfonates: The transition to polyelectrolyte/surfactant behavior - Jiang, L; Huang, J; Bahramian, A; Li, P; Thomas, R; Penfold, J (2012)
The properties and phase diagrams of aqueous mixtures of dodecyltrimethylammonium bromide (C 12TAB) with the sodium oligoarene sulphonates (POSn), POS2, POS3, POS4, and POS6 have been studied using surface tension and neutron reflectometry to study the surface, and neutron small angle scattering and fluorescence to study the bulk solution. The behavior of POS2 and POS3 is reasonably consistent with mixed micelles of C 12TAB and POSn-(C 12TA) n. These systems exhibit a single critical micelle concentration (CMC) at which the surface tension reaches the usual plateau. This is contrary to a recent report which suggests that the onset of the surface tension plateau does not coincide with the CMC. In the POS3 system, the micelles conform to the core-shell model, are slightly ellipsoidal, and have aggregation numbers in the range 70-100. In addition, the dissociation constant for ionization of the micelles is significantly lower than for free C 12TAB micelles, indicating binding of the POS3 ion to the micelles. Estimation of the CMCs of the POSn-(C 12TA) n from n = 1-3 assuming ideal mixing of the two component surfactants and the observed values of the mixed CMC gives values that are consistent with the nearest related gemini surfactant. The POS4 and POS6 systems are different. They both phase separate slowly to form a dilute and a concentrated (dense) phase. Fluorescence of POS4 has been used to show that the onset of aggregation of surfactant (critical aggregation concentration, CAC) occurs at the onset of the surface tension plateau and that, at the slightly higher concentration of the phase separation, the concentration of POS4 and C 12TAB in the dilute phase is at or below its concentration at the CAC, that is, this is a clear case of complex coacervation. The surface layer of the C 12TA ion in the surface tension plateau region, studied directly by neutron reflectometry, was found to be higher than a simple monolayer (observed for POS2 and POS3) for both the POS4 and POS6 systems. In POS6 this evolved after a few hours to a structure consisting of a monolayer with an attached subsurface bilayer, closely resembling that observed for one class of polyelectrolyte/surfactant mixtures. It is suggested that this structured layer, which must be present on the surface of the dilute phase of the coacervated system, is a thin wetting film of the dense phase. The close resemblance of the properties of the POS6 system to that of one large group of polyelectrolyte/surfactant mixtures shows that the surface behavior of oligoion/surfactant mixtures can quickly become representative of that of true polyelectrolyte/surfactant mixtures. In addition, the more precise characterization possible for the POS6 system identifies an unusual feature of the surface behavior of some polyelectrolyte/surfactant systems and that is that the surface tension can remain low and constant through a precipitation/ coacervation region because of the characteristics of two phase wetting. The well-defined fixed charge distribution in POS6 also suggests that rigidity and charge separation are the factors that control whether a given system will exhibit a flat surface tension plateau or the alternative of a peak on the surface tension plateau. © 2011 American Chemical Society.